2022
DOI: 10.21776/ub.jpas.2022.007.03.4
|View full text |Cite
|
Sign up to set email alerts
|

Security Agencies and Human Right Violations in Nigeria

Abstract: It is no news that Nigeria, which is arguably the giant of Africa, is known for human rights violations. From its years of military authoritarianism which witnessed the killing of several human rights activists, and since the return to democratic rule, the country’s human rights narrative has not changed. Government authorities and law enforcement agents (the police) frequently engage in various human rights violations, notably unlawful killings, torture, ill-treatment of no crime suspects, forced evictions, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The objectives CRE however, are geared towards preservation of life and maintenance of human relationship with his creator and environment. The subject designed to inculcate in the life of the young people the essential norms or learning capable of giving man a sense of social responsibility [2]. This is in line with Oser and Reichenbach as quoted by Njoku that … "the content and objectives Christian Religion Education are detailed and rich enough to deal with the present moral crises in the society which centers on denial of fundamental human rights" [13].…”
Section: Discussion Of Findingsmentioning
confidence: 66%
See 3 more Smart Citations
“…The objectives CRE however, are geared towards preservation of life and maintenance of human relationship with his creator and environment. The subject designed to inculcate in the life of the young people the essential norms or learning capable of giving man a sense of social responsibility [2]. This is in line with Oser and Reichenbach as quoted by Njoku that … "the content and objectives Christian Religion Education are detailed and rich enough to deal with the present moral crises in the society which centers on denial of fundamental human rights" [13].…”
Section: Discussion Of Findingsmentioning
confidence: 66%
“…Thus, Human right is not only violated by government but many religious leaders, intellectuals, politicians and journalists [1]. For more than a decade of democratic governance in Nigeria, and endorsement of universal declaration of human rights charter, Nigerians still face a lot of human rights abuses [2]. A Study has observed that cases of human rights violations is high in Nigeria which has become a culture of impunity in the Africa's most populous country [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations